Analisis penerapan akuntansi Pajak Penghasilan Pasal 21 pada karyawan PT. Manado Post - Djaafara, Baharudin; Sondakh, Jullie J.; Wangkar, Anneke (Riset Akuntansi dan Portofolio Investasi, 2024)
Manado Post is a Media Company under the Jawa Post Group. Manado Post has a large number of employees with the specifications of Permanent Employees and Non-Permanent Employees, so it has great potential in paying taxes, especially Article 21 Income Tax. In addition, there is the potential for errors in both calculating and recording Income Tax. This also affects accounting records, because errors in calculations will cause errors in accounting records. In addition, Manado Post on irregularities in both calculation and reporting of Income Tax caused by differences in views on the Income Tax Law. This also affects accounting records. Based on the reference background of this study, the subject matter can be formulated which will then be the object of discussion in this study. This study used qualitative descriptive method. A total of 55 employees were involved in the study, and of these, 15 employees were the subjects of the study. The qualitative research intended here is to illustrate how the accounting treatment of Article 21 Income Tax applied in Manado Post. The results showed that Manado Post did not fully follow the applicable Tax Law in calculating article 21 income tax on its employees. This causes an overpayment of Article 21 income tax by the company. In this case, Manado Post needs to improve understanding and compliance with applicable tax rules to avoid errors in tax calculations.